Molecular phylogeny of Aphyocharacinae (Characiformes, Characidae) with morphological diagnoses for the subfamily and recognized genera - Tagliacollo, Victor A. [UNESP]; Souza-Lima, Rosana; Benine, Ricardo C.; Oliveira, Claudio [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
The subfamily Aphyocharacinae was recently redefined to comprise eight genera: Aphyocharax, Prionobrama, Paragoniates, Phenagoniates, Leptagoniates, Xenagoniates, Rachoviscus and Inpaichthys. This new composition, however, is partially incongruent with published results of molecular studies especially concerning the positions of Rachoviscus and Inpaichthys. Our goal was to investigate the monophyly of Aphyocharacinae and its interrelationships using three distinct phylogenetic methodologies: Maximum-likelihood and Bayesian analyses of molecular data, and also Parsimony analysis of a concatenated molecular and morphological dataset. All tree topologies recovered herein suggest that Rachoviscus, Inpaichthys and Leptagoniates pi do not belong to the Aphyocharacinae. The remaining aphyocharacin taxa analyzed do form a monophyletic group, which is itself composed of two subgroups being one comprised of Paragoniates, Phenagoniates, Leptagoniates and Xenagoniates, and the other comprised of Aphyocharax and Prionobrama. Internal relationships among these genera are statistically well supported and morphological synapomorphies are presented at the generic level. All tree topologies also indicate that Aphyocharacidium is closely related to Aphyocharacinae suggesting that it should be included in this subfamily. As recognized in the present study, the Aphyocharacinae is diagnosed by a single morphological synapomorphy: two dorsal-fin rays articulating with the first dorsal pterygiophore. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neotropical fishes; Evolutionary relationships; South America; Aphyocharax